Investigating causal relation between prenatal arsenic exposure and birthweight: Are smaller infants more susceptible?. (November 2017) - Rahman, Mohammad L.; Valeri, Linda; Kile, Molly L.; Mazumdar, Maitreyi; Mostofa, Golam; Qamruzzaman, Qazi; Rahman, Mahmudur; Baccarelli, Andrea; Liang, Liming; Hauser, Russ; Christiani, David C.
Abstract: Background: Shortening of gestation and intrauterine growth restriction (IUGR) are the two main determinants of birthweight. Low birthweight has been linked with prenatal arsenic exposure, but the causal relation between arsenic and birthweight is not well understood. Objectives: We applied a quantile causal mediation analysis approach to determine the association between prenatal arsenic exposure and birthweight in relation to shortening of gestation and IUGR, and whether the susceptibility of arsenic exposure varies by infant birth sizes. Methods: In a longitudinal birth cohort in Bangladesh, we measured arsenic in drinking water (n = 1182) collected at enrollment and maternal toenails (n = 1104) collected ≤ 1-month postpartum using inductively coupled plasma mass spectrometry. Gestational age was determined using ultrasound at ≤ 16 weeks' gestation. Demographic information was collected using a structured questionnaire. Results: Of 1184 singleton livebirths, 16.4% (n = 194) were low birthweight (< 2500 g), 21.9% (n = 259) preterm (< 37 weeks' gestation), and 9.2% (n = 109) both low birthweight and preterm. The median concentrations of arsenic in drinking water and maternal toenails were 2.2 μg/L (range: below the level of detection [LOD] − 1400) and 1.2 μg/g (range: < LOD − 46.6), respectively. Prenatal arsenic exposure was negatively associated with birthweight, where the magnitude of the association varied across birthweight percentiles. The effect of arsenic on birthweight mediated via shortening of gestation affected all infants irrespective of birth sizes ( β range: 10th percentile = − 19.7 g [95% CI: − 26.7, − 13.3] to 90th percentile = − 10.9 g [95% CI: − 18.5, − 5.9] per natural log water arsenic increase), whereas the effect via pathways independent of gestational age affected only the smaller infants ( β range: 10th percentile = − 28.0 g [95% CI: − 43.8, − 9.9] to 20th percentile = − 14.9 g [95% CI: − 30.3, − 1.7] per natural log water arsenic increase). Similar pattern was observed for maternal toenail arsenic. Conclusions: The susceptibility of prenatal arsenic exposure varied by infant birth sizes, placing smaller infants at greater risk of lower birthweight by shortening of gestation and possibly growth restriction. It is important to mitigate prenatal arsenic exposure to improve perinatal outcomes in Bangladesh. Highlights: We investigated the causal relation between prenatal arsenic exposure and birthweight. Smaller infants were more susceptible to arsenic exposure. Both shortened gestation and IUGR likely to play important role in explaining arsenic-birthweight relation. Minimizing prenatal arsenic exposure may improve perinatal outcomes in Bangladesh.